Effects of Temperature on the Fracture Response of EMC-Si Interface Found in Multilayer Semiconductor Components - João Valdoleiros; Alireza Akhavan-Safar; Payam Maleki; Pedro F. C. Videira; Ricardo J. C. Carbas; Eduardo A. S. Marques; Bala Karunamurthy; Lucas F. M. da Silva (Surfaces)
Despite the fact that temperature is an important condition that affects the behavior of material interfaces used in integrated circuits (ICs), such as the case for epoxy molding compound (EMC) and silicon (Si), this has not been thoroughly studied. To fill this gap, the present work aims to examine the fracture of the bi-material interfaces in multilayered semiconductor components and, more specifically, the EMC-Si, through the experimental quasi-static mode I fracture experiments conducted at different temperatures. The experiments were followed by numerical simulations using cohesive zone modeling (CZM) implemented using Abaqus. Simulation results were aimed at matching experimental data using an inverse CZM approach to determine cohesive properties such as initial stiffness and maximum traction. Experimental results revealed temperature-dependent variations in fracture behavior, with low temperature (−20 °C) showing a decrease in stiffness with values around 650 MPa/mm and a maximum tensile strength of 48 MPa; high temperature (100 °C) revealed a maximum traction and stiffness of 120 MPa and 1200 MPa/mm, respectively. A possible explanation for the results obtained at high temperatures is that temperature changes cause a significant redistribution of residual stresses in the sample and at the interfaces, reducing the stiffness at lower temperatures.